Comparison of Two Interpolation Methods for Resampling Center of Mass Velocity Data - Uğur Ödek (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2016)
Data interpolation methods are highly useful for estimating missing values. Another usage of these methods is resampling the measured data. In the field of biomechanics sometimes researchers have to deal problems related to data acquisition rate or sample size. Using linear or polynomial interpolation methods, it is possible to overcome these problems. However, choosing right interpolation method is very critical. In this short report two interpolation methods with very similar estimations were compared. Results showed that, even the interpolation curve fits most of the data, the overall appearance can be misleading.